Uncertainty in transitions of African American caregivers - Unson, Christine; Flynn, Deborah; Chukwurah, Queendalene; Glendon, Maryann; Testut, Tammy (Issues in Mental Health Nursing, 2020)
The purpose of this study was to gain an understanding of the ambiguities and uncertainties experienced by a diverse group of African-American caregivers. The study applied Schlossberg's transition theory (TT) and Mishel’s revised uncertainty theory to narratives of self-identified African-American caregivers who provided care at least 5 h a week. The men (6) and women (8) were mostly unmarried, mostly caring for a parent or grandparent. The caregivers’ average age was 52 (SD = 19; ages ranged from 24 to 82 years); and the care recipients’ average age was 84 (SD = 9). Six care recipients had dementia and the remainder had multiple disease diagnoses. Narratives were obtained by in-depth interviews or focus group discussions. These were audio-recorded, transcribed verbatim professionally and analyzed independently by trained coders. Schlossberg’s TT contextualized whereas Mishel’s RUIT illuminated the characteristics of the transition, its associated uncertainty, and their relationship to the development of caregiver stress. Situational factors such as difficulties with illness symptoms of the care recipient, conflict between previous experience and current expectations and the adjustments to the new caregiving role, burdened younger caregivers more than older caregivers. Self-factors related to lack of knowledge about the illness and feelings of lack of control. Social support was predominantly provided by family members, and its absence resulted in conflict among siblings and caregiver stress. The most common coping strategies include religiosity, expectations of reciprocity, and coming to terms with the uncertainty. Understanding the feelings, perceptions and needs of caregivers in transition is tantamount to providing nursing care.
Keywords: Adaptation, Psychological; Adult; African American; African Americans; Aged; Aged, 80 and over; Caregivers; Female; Grandparents; Humans; Male; Middle Aged; Narration; Parents; Social Support; Stress, Psychological; Uncertainty; Young Adult; adult; aged; caregiver; child parent relation; coping behavior; dept.nur; dept.pch; female; grandparent; human; male; mental stress; middle aged; peer-reviewed; psychology; social support; uncertainty; verbal communication; very elderly; young adult

It’s What We Do: Māori Carers Talk About Roles, Challenges, and Coordination in Caring for Older Family Members - Simpson, Mary; McAllum, Kirstie; Unson, Christine; Fox, Stéphanie; Hancock, Te Oha (Innovation in Aging, 2020)
As the population of Aotearoa/New Zealand heads towards one-in-four being aged over 65-years-and-over by 2040, it is anticipated that family members will play an increasingly important role in caring for older relatives with chronic and age-related health issues. Multi-generational, and in particular three-generational living arrangements, combined with family care of older relatives are a growing trend; a trend already even evident among Māori communities. This paper reports on a study that explored the care experiences and expectations of 14 past and current Māori carers (aged 23 to 72-years) of older relatives. Interviews were audio-recorded, transcribed verbatim, and coded independently. The initial thematic analysis revealed nine themes and participants were invited to feedback on the summary in person or in writing. The feedback resulted in the original themes being collapsed into four (with subthemes): “Care is Normal”; “Collective Coordination of Care”; “Insider-Carer—Outsider Perspectives on Caring”; and “Societal Influences on Family Care/Carers”. Firstly, these themes highlight how Māori cultural norms infuse direct care, support, and coordination roles within family care of the older family member. Secondly, they reveal the challenges for family carers in talking about their work with others, especially (thirdly) in the face of negative attitudes towards care and carers of an older family member within wider society. These findings have implications for cultural and wider socio-political influences in socialising different groups to carer role expectations. If society is to better prepare future caregivers for their role, ongoing research is needed with the various cultural groups in Aotearoa/New Zealand.
Keywords: dept.pch; peer-reviewed